Kemampuan Mendengar Ritme dalam Solfegio - Maria Klara Amarilis Citra Sinta Dewi Tukan; Wilfridus Beda Nuba Dosinaeng (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This research is a quantitative study conducted to determine the effect of the ability to hear rhythm on students' solfeggio learning achievement. The research population was 83 second-semester students of the Sendratasik Study Program FKIP Unwira Kupang. Based on the Slovin formula with a significance level of 5%, 69 students were randomly selected using a simple random sampling technique. There are two variables in this research, namely the ability to hear rhythm as the independent variable and solfeggio learning achievement as the dependent variable. Data for these two variables were obtained from the results of students' rhythm listening ability tests and solfeggio learning achievement tests. After the data was collected, the data was then analyzed using simple regression analysis. From the statistical calculations carried out, the values obtained were F count =68.383 and F table = F (0.05)(17.40) =1.885. Because F count < F table then Ha is accepted so it can be concluded that there is a significant influence on the ability to hear rhythm on students' solfeggio learning achievement. The RSquare value = 0.505 indicates that the ability to hear rhythm 50.5% influences the solfeggio learning achievement of students in the second semester of the Sendratasik Study Program, FKIP Unwira Kupang.